2009
DOI: 10.1159/000235604
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Arteriovenous Malformations

Abstract: Background: Arteriovenous malformations (AVMs) are commonly thought to be congenital malformations; however, patients usually present in adolescence or adulthood. This study was carried out to better understand the development of AVMs between birth and presentation. Methods: A retrospective review was performed of the medical records of all patients under 25 presenting to a single institution with an AVM or spontaneous intracerebral hemorrhage from 2000 to 2007. Results: Out of a total of 34 cases, 3 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 90 publications
1
27
1
Order By: Relevance
“…However, this does not mean a 15-Gy dose of radiation is enough for vascular obliteration in AVMs. Clinical work has demonstrated that a margin dose of [16][17][18][19][20][21][22][23][24][25] Gy is necessary to achieve a satisfactory occlusion rate. 10,44 More work with smaller titrations of radiation doses and larger animal numbers per group is required to find the optimal radiation dose for vascular targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not mean a 15-Gy dose of radiation is enough for vascular obliteration in AVMs. Clinical work has demonstrated that a margin dose of [16][17][18][19][20][21][22][23][24][25] Gy is necessary to achieve a satisfactory occlusion rate. 10,44 More work with smaller titrations of radiation doses and larger animal numbers per group is required to find the optimal radiation dose for vascular targeting.…”
Section: Discussionmentioning
confidence: 99%
“…16,37 The aim of AVM treatment is to prevent hemorrhage. 29 Treatment is effective only with complete AVM removal or obliteration.…”
mentioning
confidence: 99%
“…13,19 In a study of younger patients with AVMs, almost 10% of the patients had undergone previous angiography without evidence of vascular malformation. 11 There are also multiple case reports of AVMs presenting with subdural hemorrhage, 5,17 but no reports that we are aware of attribute an acute supratentorial subdural hemorrhage to an AVM.…”
Section: Discussionmentioning
confidence: 99%
“…Although an initiating event has yet to be defined, possible candidates include trauma, tissue hypoxia, venous hypertension, infection, inflammation, irradiation, or compression [14,15]. The primary vascular defect may be the development of a simple arteriovenous fistula [16], with altered hemodynamic stresses occurring in the affected vessels. Further pro-angiogenic vascular remodeling and secondary vascular changes would occur secondary to the hemodynamic stress, producing the characteristic AVM seen in clinical practice [17].…”
Section: Theories Of Pathogenesismentioning
confidence: 99%